The Impact of Internal and External Factors on Agricultural Extension Performance through the Kostratani Program in Banten Province - Novita, Rita (Master of Management Department, Faculty of Economics and Business, Universitas Bangka Belitung, 2023)
The agricultural sector is pivotal in human sustenance by providing food, livestock feed, and bioenergy. In Indonesia, agriculture is strategically positioned in the national economy, contributing to food security, employment, and poverty alleviation, particularly within the agricultural sector. This study aims to analyze the factors influencing the Kostratani program, assess internal factors affecting the performance targets of instructors within the Kostratani program as an intervening variable, and examine external factors influencing the performance targets of instructors within the Kostratani program. Employing a quantitative approach, this research utilizes survey and interview methods conducted in Banten Province across various Agricultural Extension Centers, particularly focusing on constructing Agricultural Extension Centers in Lebak Regency, Pandeglang Regency, and Tangerang Regency. The findings reveal that internal factors significantly influence the Kostratani Program and the performance targets of extension officers, while external factors show no significant impact on either. Moreover, the Kostratani Program exhibits a noteworthy influence on the performance targets of extension officers.